2015
DOI: 10.1371/journal.pone.0127379
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Syphilis Screening Using Point-Of-Care Testing in Low- and Middle-Income Countries in Asia and Latin America: A Cost-Effectiveness Analysis

Abstract: BackgroundUntreated syphilis in pregnancy is associated with adverse clinical outcomes to the infant. In low- and middle-income countries in Asia and Latin America, 20%-30% of women are not tested for syphilis during pregnancy. We evaluated the cost-effectiveness of increasing the coverage for antenatal syphilis screening in 11 Asian and 20 Latin American countries, using a point-of-care immunochromatographic strip (ICS) test.MethodsThe decision analytical cost-effectiveness models reported incremental costs p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 19 publications
0
48
0
Order By: Relevance
“…Furthermore, studies have shown that prenatal syphilis screening, treatment support testing and treatment during pregnancy are highly cost-effective in most countries regardless of prevalence or availability of resources, and can even be cost-saving in LMICs with syphilis prevalence ≥3% in pregnant women 47–50 . In China, where syphilis and HIV prevalence in pregnant women is low but rising, integration of prenatal syphilis and HIV screening was found to be highly cost-effective 51 .…”
Section: Epidemiologymentioning
confidence: 99%
“…Furthermore, studies have shown that prenatal syphilis screening, treatment support testing and treatment during pregnancy are highly cost-effective in most countries regardless of prevalence or availability of resources, and can even be cost-saving in LMICs with syphilis prevalence ≥3% in pregnant women 47–50 . In China, where syphilis and HIV prevalence in pregnant women is low but rising, integration of prenatal syphilis and HIV screening was found to be highly cost-effective 51 .…”
Section: Epidemiologymentioning
confidence: 99%
“…Brazil is signatory of international plans for the elimination of syphilis. Recently, the World Health Organization (WHO) has defined, as goals for the certification of elimination of syphilis, the 95% of coverage of prenatal care and screening for syphilis in pregnant women, in order to reach the goal of congenital syphilis of 0.5 cases per 1,000 live births, which has been reached only by Cuba and Chile in the Latin America 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In the Brazilian scenario, gestational syphilis presents a high magnitude and most cases continue to be diagnosed late, especially in the North and Northeast regions, where difficulties persist in the control of the disease a . The recognition of the complex and dynamic determination of sexually transmitted infections and the deepening of the knowledge on risk factors, in the relation to sociodemographic, behavioral, life condition, and organizational changes in the health system and services, can contribute to the updating of interventions aimed at them 9 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly worrying is the lack of knowledge regarding the rapid syphilis test, recommended by the WHO to improve access to syphilis diagnosis. There is evidence of the cost‐effectiveness of these tests for the treatment of syphilis during pregnancy and reports of high acceptance among professionals and users . The Brazilian MoH established the implementation of RST in PNC in 2011, which may explain the lower familiarity of professionals with these tests, given its more recent deployment.…”
Section: Discussionmentioning
confidence: 99%